"Graphitic bubbles" derived from polyimide film. (May 2017) - Tao, Zechao; Wang, Hongbao; Lian, Pengfei; Zhang, Junpeng; Liu, Zhanjun; Guo, Quangui; Liu, Lang
Abstract: A new type of graphitic foam with closed-cell pores, or called as graphitic bubbles, is derived from polyimide film using a solid-state foaming technology based on the pressure difference between inside and outside of graphite layers at elevated temperature. The bulk densities of graphite bubbles vary from 0.60 to 0.42g/cm 3 when the foaming temperature increases from 2200 to 2600 °C. The closed porosity in graphitic bubbles ranges from 64.2% to 74.0% which also can be confirmed from optical microscopy and scanning electron microscopy. The thermal conductivity of graphite bubbles is anisotropy along the in-plane direction (296.6 W/mK) and the out-of-plane direction (2.79 W/mK).